Proceedings of the 13th Workshop on Computational Approaches to Subjectivity, Sentiment, &Amp; Social Media Analysis 2023
DOI: 10.18653/v1/2023.wassa-1.29
|View full text |Cite
|
Sign up to set email alerts
|

ChatGPT is fun, but it is not funny! Humor is still challenging Large Language Models

Abstract: Humor is a central aspect of human communication that has not been solved for artificial agents so far. Large language models (LLMs) are increasingly able to capture implicit and contextual information. Especially, OpenAI's ChatGPT recently gained immense public attention. The GPT3-based model almost seems to communicate on a human level and can even tell jokes. Humor is an essential component of human communication. But is ChatGPT really funny?We put ChatGPT's sense of humor to the test. In a series of explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This may represent a new opportunity for humor in CAs. Yet, despite this technical opportunity, large language models seem to mainly use pre-scripted humor to this point, as Jentzsch and Kersting [26] found. Their study revealed that 90% of the 1008 jokes they generated with ChatGPT were the same 25 jokes.…”
Section: Humor In Hcimentioning
confidence: 99%
See 1 more Smart Citation
“…This may represent a new opportunity for humor in CAs. Yet, despite this technical opportunity, large language models seem to mainly use pre-scripted humor to this point, as Jentzsch and Kersting [26] found. Their study revealed that 90% of the 1008 jokes they generated with ChatGPT were the same 25 jokes.…”
Section: Humor In Hcimentioning
confidence: 99%
“…To avoid these risks, companies must exercise caution and consider the impact their content can have. This could also be a reason why LLMs are constrained to certain pre-scripted humorous interactions Jentzsch and Kersting [26]. The risk or fear of being offensive can be an important factor in why CA companies prefer to play it safe with harmless and corny jokes.…”
Section: Misunderstandingsmentioning
confidence: 99%
“…humor, is important during communication. Ope-nAI (2023) has reported GPT-4's ability to understand jokes, while subsequent works show limited capacity for LLMs to generate or explain humor (Jentzsch and Kersting, 2023;Hessel et al, 2023). As creativity is essential to the development of art, science, and everyday life for human (Gabora and Kaufman, 2010), it is non-trivial if models could produce creative content.…”
Section: Introductionmentioning
confidence: 99%